The Role of Control Environment (CE) in the Public Sector in Preventing Fraud: A Literature Study - Harahap, Ludwina; Isgiyarta, Jaka (Magister Akuntansi Universitas Pancasila, 2023)
This paper aims to conduct a literature study on the role of the CE in preventing fraud. Undoubtedly, weak internal controls (IC) and CE are the factors that cause various cases of fraud to occur, such as corruption, collusion, bribery, and various unethical behaviors.. The COSO IC Framework and previous studies explicitly state that the CE is the primary basis for building a strong IC system, and the leader or supervisor is a central figure in realizing the formation of a strong CE. However, from several previous studies, not much has examined the role of the CE on the effectiveness of ICs in preventing fraud. The method used is to enter keywords in the search engine, consisting of